Impact of Financial Technology Utilization, Working Capital Management, and Financial Resilience on MSME Sustainability During Uncertainty Economy - Lembong, Herningsih Sutri; Tundu, Astrid Kristiana; Anwar, Samsul; Syaiful, Muhammad; Febrina, Ilza; Sudarmanto, Eko (International Journal of Business, Law, and Education, 2025)
Based on the results and discussion, this study concludes that financial technology utilization, working capital management, and financial resilience each have a positive and significant impact on the sustainability of MSMEs during periods of economic uncertainty. The findings highlight that MSMEs that actively adopt digital financial tools, manage their short-term finances efficiently, and develop strong financial resilience are better equipped to withstand and adapt to external shocks such as economic downturns, inflation, and market disruptions. Among the three factors, financial resilience emerged as the most influential, underscoring the critical role of strategic preparedness, adaptability, and financial buffers in ensuring business continuity. These results reinforce the theoretical perspective of the Resource-Based View (RBV), which emphasizes the importance of internal capabilities as sources of sustainable advantage. Therefore, strengthening digital adoption, financial management practices, and resilience-building efforts should be prioritized by MSME stakeholders, including policymakers, financial institutions, and business support organizations to enhance long-term survival and performance in an increasingly volatile economic environment.